2005
DOI: 10.1002/chem.200401093
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Energy Levels in all‐trans Long Linear Polyenes: The Case of the 3,20‐Di(tert‐butyl)‐2,2,21,21‐tetramethyl‐all‐trans‐3,5,7,9,11,13,15,17,19‐docosanonaen (ttbp9) Conforming to Kasha's Rule

Abstract: The absorption, fluorescence and fluorescence excitation spectra for 3,20-di(tert-butyl)-2,2,21,21-tetramethyl-all-trans-3,5,7,9,11,13,15,17,19-docosanonaen (ttbP9) in dilute solutions of 2-methylbutane were recorded at temperatures over the range 120-280 K. The high photostability of this nonaene allows us to assert that it exhibits a single fluorescence and that this can be unequivocally assigned to emission from its 1(1)B(u) excited state, it being the first excited electronic state. Available photophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…those for a 7 × 10 −6 M solution measured in ClB at the same temperature range. As can be seen, the spectral behavior of β‐carotene in the two solvents was as expected for a polyene: that is, lowering the temperature significantly increases the vibronic structure and the intensity of the absorption band. The increased spectral intensity was partly a result of the volume contraction and increase in density undergone by the solvent as the temperature was lowered.…”
Section: Resultssupporting
confidence: 58%
“…those for a 7 × 10 −6 M solution measured in ClB at the same temperature range. As can be seen, the spectral behavior of β‐carotene in the two solvents was as expected for a polyene: that is, lowering the temperature significantly increases the vibronic structure and the intensity of the absorption band. The increased spectral intensity was partly a result of the volume contraction and increase in density undergone by the solvent as the temperature was lowered.…”
Section: Resultssupporting
confidence: 58%
“…Recently, Itoh [28] reported that the emission from the 1B u state in the compound may be a result of both direct excitation and delayed thermal activation. However, this model, involving the 2A g and 1B u states of the same molecular structure, is inconsistent with some photophysical evidence for these compounds [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 65%
“…(d) Finally, a dilute solution of a nonaene with four tertbutyl substituents at terminal positions [3,20-di(tertbutyl)-2,2,21,21-tetramethyl-all-trans-3,5,7,9,11,13, 15,17,19-docosanonaen] in 2-methylbutane was found to clearly exhibit the 0-0 component of its 1A g ! 1B u transition, which was shifted to a higher wavelength, with no change in the transition onset, as the temperature was slowly lowered [35]. These results were ascribed to the previous forms being highly flexible and adopting a planar structurewhich causes a red shift in the 0-0 component -in electronic transitions to more rigid planar forms.…”
Section: On Thementioning
confidence: 87%
See 1 more Smart Citation
“…This information together with other evidence provided in recent years by our laboratory [ 1,2,11–16 ] allows us to draw the following conclusions in order to propose an adequate model to correctly interpret the photophysics of polyene compounds: The position of the first intense peak in the excitation spectrum of the DPO in the six n ‐alkanes used represents a bathochromism that varies linearly with the temperature from 293 to the melting point temperature of the corresponding alkane. This behavior is red‐shifted in parallel fashion as the alkane chain is lengthened, as a result of the alkane's increasing polarizability on lengthening of its chain.The reported increase of the bathochromism with the decrease of the temperature undoubtedly also includes a structural contribution because the phenyl groups in the diphenyl polyenes in liquid solvents present such a small torsion barrier what makes their two phenyl groups are continuously rotating out of the coplanar situation.…”
Section: Discussionmentioning
confidence: 86%